Oxidation behavior and area specific resistance of La, Cu and B alloyed Fe-22Cr ferritic steels for solid oxide fuel cell interconnects - Swaminathan, Srinivasan; Ko, Yoon Seok; Lee, Young-Su; Kim, Dong-Ik (ELSEVIER SCIENCE BV, 2017)
Two Fe-22 wt% Cr ferritic stainless steels containing varying concentrations of La (0.14 or 0.52 wt%), Cu (0.17 or 1.74 wt%) and B (48 or 109 ppm) are investigated with respect to oxidation behavior and high temperature area specific resistance (ASR) of the surface oxide scales. To determine the oxidation resistance of developed steels, continuous isothermal oxidation is carried out at 800 degrees C in air, for 2000 h, and their thermally grown oxide scale is characterized using dynamic SIMS, SEM/EDX, XRD and GI-XRD techniques. To assess their electrical performance, the ASR measurement by four-point probe method is conducted at 800 degrees C in air, for 400 h. In higher La content steel, the La-oxides at the scale/alloy interface promotes the oxygen transport which resulted in sub-surface oxidation of Mn, Cr, Ti and Al. Moreover, the inward growth of oxides contributes to increase of Fe-Cr alloy protrusions within the scale, which reduced the ASR. In contrast, sub-surface oxidation is reduced in high Cu-alloyed steel by segregated Cu at the scale/alloy interface. Thus, addition of Cu is effective to oxidation resistance and also to better electrical performance. However, no obvious impact of B on the scale sequence and/or ASR is observed. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: HIGH-TEMPERATURE OXIDATION; CROFER 22 APU; STAINLESS-STEEL; METALLIC INTERCONNECTS; STAGE OXIDATION; CHROMIA SCALE; EVOLUTION; DIFFUSION; IRON; DEPOSITION